Respostas

2014-06-08T14:24:27-03:00
Olá, Ameliaregina8!

Vamos usar o Teorema de Pitágoras:  h^{2} =  c^{2} + c^{2}

a)
Hipotenusa: 11
Catetos: x e 5

 h^{2} = c^{2} + c^{2}
 11^{2} = 5^{2} + x^{2}
121 = 25 +  x^{2}
25 +  x^{2} = 121
 x^{2} = 121 - 25
x^{2} = 96
x =  \sqrt{96}
x =  \sqrt{ 2^{2}. 2^{2} .2.3
\boxed{4 \sqrt{6}}

b) 
Hipotenusa: 33
Catetos: y e 21

 h^{2} = c^{2} + c^{2}
 33^{2} =  21^{2} + y^{2}
1089 = 121 + y^{2}
121 + y^{2} = 1089
y^{2} = 1089 - 121
y^{2} = 968
y =  \sqrt{968}
y =  \sqrt{2^2.2.11^2}
\boxed{y = 22 \sqrt{2}}